Social Entreprenurship Pesantren (The Analysis of Argumentative Local Wisdom of Dayah in Aceh) - Iswan Fadlin; Taufiq Taufiq (Institut Agama Islam Negeri Lhokseumawe, 2023)
The objective of conducting this research is to analyze and investigate social entrepreneurship at Islamic boarding schools (Pesantren), which deals with economic independence, social influence, and strengthening religious values. It is significant that Dayah's local wisdom dimensions act as propelling pillars of transformation towards realizing the pesantren's socio-economic independence. The main objective of this research is to examine the active role of the local wisdom possessed by Dayah that contributed to its success in transitioning pesantren from